Discovery of novel benzohydroxamate-based histone deacetylase 6 (HDAC6) inhibitors with the ability to potentiate anti-PD-L1 immunotherapy in melanoma. (31st December 2023) - Peng, Xiaopeng; Yu, Ziwen; Surineni, Goverdhan; Deng, Bulian; Zhang, Meizhu; Li, Chuan; Sun, Zhiqiang; Pan, Wanyi; Liu, Yao; Liu, Shenglan; Yu, Bin; Chen, Jianjun
Abstract: In this study, a novel series of histone deacetylases 6 (HDAC6) inhibitors containing polycyclic aromatic rings were discovered and evaluated for their pharmacological activities. The most potent compound 10c exhibited high HDAC6 inhibitory activity (IC50 = 261 nM) and excellent HDAC6 selectivity (SI = 109 for HDAC6 over HDAC3). 10c also showed decent antiproliferative activity in vitro with IC50 of 7.37–21.84 μM against four cancer cell lines, comparable to that of tubastatin A (average IC50 = 6.10 μM). Further mechanism studies revealed that 10c efficiently induced apoptosis and S-phase arrest in B16-F10 cells. In addition, 10c markedly increased the expression of acetylated-α-tubulin both in vitro and in vivo, without affecting the levels of acetylated-H3 (marker of HDAC1 inhibition). Furthermore, 10c (80 mg/kg) exhibited moderate antitumor efficacy in a melanoma tumour model with a tumour growth inhibition (TGI) of 32.9%, comparable to that (TGI = 31.3%) of tubastatin A. Importantly, the combination of 10c with NP19 (a small molecule PD-L1 inhibitor discovered by us before) decreased tumour burden substantially (TGI% = 60.1%) as compared to monotherapy groups. Moreover, the combination of 10c with NP19 enhanced the anti-tumour immune response, mediated by a decrease of PD-L1 expression levels and increased infiltration of anti-tumour CD8 + T cells in tumour tissues. Collectively, 10c represents a novel HDAC6 inhibitor deserving further investigation as a potential anti-cancer agent.